Attritional Structures the Major Factor in Increasing Endangerment by Earthquakes in Cities - Abdollahi, Vali; Hosseinzadeh, Mohammad (International Journal of Geography and Geology, 2016)
Designed and organized structures show increased resistance compared to organic and compressed ones when facing natural dangers. Based on Islamic indices of the Department of roads and city construction regarding old constructs, the main organic weaves of cities are included in this definition. So, near one eighth of the city population of Iran resides in such structures. This matter has made attention to renovation and strengthening of this immense volume of city structure more necessary. In this planning, attention should be devoted to special design of spaces for safe evacuation, design of public passageways in accord with prevention of blockage at the time of earthquake, and dangerous city facilities such as gas provision networks and the building material of the ground. Only with strengthening of these structures, people can to some extent in case of occurrence of an earthquake have peace of mind and live without fear. In this paper which has been formulated based on an applied and descriptive-analytic method, it has been endeavored concurrently with analysis of past actions to introduce new executive strategies for the purpose of decreasing riskiness in these structures.